Assessment of Occupational Safety Risks in Ship Repairs at the Fisheries Service Employees Cooperative Shipyard (FSECS) - Ilham Sudrajat; Fis Purwangka; Budhi Hascaryo Iskandar (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2024)
Various activities at the FSEC shipyard found many potential dangers in each element of work activity. The FSEC shipyard requires risk assessments and critical points in each ship repair activity to overcome these problems. So, research is structured with the aim; a) identify and describe repair activities at FSEC yards; b) determine critical points along the repair, along with sources of danger and consequences. This research data analysis uses the FMEA method to identify each type of work and risk assessment. Based on the identification that are assumed to be crucial in the flow of ship repair activities, 26 activities were recorded including; a) preparation 10; b) process 10 and; c) post ship docking 6. Based on 26 activities, a total of 40 ships were recorded as sources of danger from docking preparations, ship docking processes and post-ship docking. Based on the results of data processing and analysis, it was concluded that 6 activities were included in the critical risk category, including; holding the ship as it is being lowered, the ship entering the docking area, removing the remaining barnacles, turning on the grinder, grinding the upper and lower hull of the ship and getting on and off the ship.